Pengaruh kreativitas dan profesionalisme terhadap kinerja guru Sekolah Menengah Pertama Negeri di kecamatan Trimurjo kabupaten Lampung Tengah - Kasmur, Roslinawati; Riyanto, Riyanto; Sutanto, Agus (Jurnal Humaniora dan Ilmu Pendidikan, 2021)
Purpose: The purpose of this study was to determine the effect of teacher creativity and professionalism on the performance of teachers in SMP Negeri in Trimurjo district, Central Lampung regency. Research methodology: The research design is quantitative research or verification research. The method used in this research is an ex post facto approach with a correlational design. The objects of this research are creativity, professionalism and teacher performance. The study population was the teachers at the State Junior High School in Trimurjo District, with a total sample of 63 respondents. The data collection technique used a questionnaire. The analytical tool used is descriptive analysis, simple linear regression analysis and multiple linear analysis with the SPSS program. Results: The results of hypothesis testing partially have a positive and significant effect on creativity on teacher performance. There is a positive and significant effect of teacher professionalism on performance. Simultaneously the creativity and professionalism of teachers together have a positive and significant effect on teacher performance. Limitations: This study is still not optimal due to the COVID-19 pandemic, so the authors cannot conduct face-to-face research and observe real school conditions. Contribution: The results of this study contribute to evaluating and improving the creativity and professionalism of teachers in Trimurjo.